Neural Code for Ambient Heat Detection in Elaterid Beetles - Merivee, Enno; Must, Anne; Nurme, Karin; Di Giulio, Andrea; Muzzi, Maurizio; Williams, Ingrid; Mänd, Marika (Frontiers in Behavioral Neuroscience, 2020)
Environmental thermal conditions play a major role at all levels of biological organization; however, there is little information on noxious high temperature sensation crucial in behavioural thermoregulation and survival of small ectothermic animals such as insects. So far, capability to unambiguously encode heat, has been demonstrated only for the sensory triad of the spike bursting thermo- and two bimodal hygro-thermoreceptor neurons located in the antennal dome-shaped sensilla in a carabid beetle. We used extracellular single sensillum recording, in the range of 20 to 45 °C, to demonstrate that a similar sensory triad in the elaterid Agriotes obscurus also produces high temperature induced bursty spike trains. Several parameters of the bursts are temperature dependent allowing the neurons in a certain order to encode different, but partly overlapping ranges of heat up to lethal levels in a graded manner. ISI in a burst is the most useful parameter out of six. Our findings consider spike bursting as a general, fundamental quality of the classical sensory triad of antennal thermo- and hygro-thermoreceptor neurons widespread in many insect groups being a flexible and reliable mode of coding unfavourably high temperatures. The possible involvement of spike bursting in behavioural thermoregulation of the beetles is discussed. By contrast, the mean firing rate of the neurons in regular and bursty spike trains combined does not carry useful thermal information at the high end of noxious heat.